SMALL AND MEDIUM ENTREPRENEURS IN INDONESIA GO GLOBAL: CHALLENGES AND THE PROBLEMS - Evalina, Evalina (Universitas Pamulang, 2018)
Globalization is representing challenge and opportunity to the international marketer. More integrated countries on a regional basis formed trading block, encourage international trade and investment volume, give consumers choice more products than before. Small and Medium Entrepreneurs (SME) in Indonesia like or not must face the fact, that they must compete with other SME from other countries. But, nowadays most ofSME in Indonesia haven’t ready yet to compete with other SME from other countries. This research is analyzed the SME in Indonesia by the power of competition. Can SME in Indonesia face the challenges and problems? How government plays its role to help SME in Indonesia? This research is using qualitative descriptive methods. The results are what the challenges and problems that SME in Indonesia have and how is charges for government role to help the SME in Indonesia.